2010
DOI: 10.1212/wnl.0b013e3181ea9f03
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life declines after first ischemic stroke

Abstract: Objectives: Quality of life (QOL) after stroke is poorly characterized. We sought to determine long-term natural history and predictors of QOL among first ischemic stroke survivors without stroke recurrence or myocardial infarction (MI). Methods:In the population-based, multiethnic Northern Manhattan Study, QOL was prospectively assessed at 6 months and annually for 5 years using the Spitzer QOL index (QLI), a 10-point scale. Functional status was assessed using the Barthel Index (BI) at regular intervals, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 39 publications
8
65
3
2
Order By: Relevance
“…The Northern Manhattan study highlights the linear relationship between the two, showing that disability increases with time even when there is no evidence of stroke recurrence. The follow-up for the NEMISIS study went on to show that even 7 years post stroke, survivors showed persistently low HRQOL [21,38]. It is surprising that we observed no preservation of the spiritual sphere of HRQOL in our stroke cohort as was observed in Ibadan, Nigeria, given that previous QOL studies done in Jamaica for other disease states used the spirituality of Jamaicans to account for their relatively preserved QOL.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The Northern Manhattan study highlights the linear relationship between the two, showing that disability increases with time even when there is no evidence of stroke recurrence. The follow-up for the NEMISIS study went on to show that even 7 years post stroke, survivors showed persistently low HRQOL [21,38]. It is surprising that we observed no preservation of the spiritual sphere of HRQOL in our stroke cohort as was observed in Ibadan, Nigeria, given that previous QOL studies done in Jamaica for other disease states used the spirituality of Jamaicans to account for their relatively preserved QOL.…”
Section: Discussionmentioning
confidence: 66%
“…This difference was not explained by co-morbidities as these were not different between the two groups. It is a phenomenon that has been repeatedly observed in the literature with studies showing that even in TIAs, where physi- cal disability has completely resolved, HRQOL continues to be less than population norms [19,38]. Some have attributed this to the fact that approximately 30% of patients with TIA and mild stroke have CT findings showing atherosclerotic changes in small vessels or white matter disease.…”
Section: Discussionmentioning
confidence: 96%
“…26,27 Although no definitive trials address the impact of rehabilitation intensity on poststroke outcomes, the available evidence suggests that IRF utilization is associated with better outcomes than SNF utilization. 13,28,29 A systematic review showed that organized and coordinated postacute inpatient rehabilitation care following an acute stroke is associated with decreased mortality and dependence compared to alternative forms of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…159 Moreover, NOMAS showed that those with no insurance or Medicaid are more likely than those with Medicare or private insurance to experience declines in function and quality of life after stroke, starting Ϸ3 years after the stroke. 170,171 Conversely, there are also substantial racial disparities among veterans with equal access to health care through the VA systems. For example, blacks or African Americans and Hispanics were less likely to use inpatient therapy services after a stroke than their white counterparts.…”
Section: Insurancementioning
confidence: 99%